The Influence of Extraversion Personality on Students’ Engagement in School Environmental Actions through Pro-Environmental Motivation as a Mediator - David Tanubrata; Agung Purwanto; Diana Vivanti Sigit (Jurnal Edusci, 2026)
Background. Extraverted individuals are generally characterized by sociability, assertiveness, and active participation in social contexts, which may enhance their involvement in environmental initiatives. However, the extent to which these personality traits translate into sustained environmental engagement is likely influenced by students’ intrinsic motivation toward environmental responsibility. Aims. This study investigates the influence of extraversion personality on students’ engagement in school-based environmental actions, with pro-environmental motivation examined as a mediating mechanism. Methods. A quantitative cross-sectional design was employed using survey data collected from 200 senior high school students enrolled in eco-friendly schools. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both direct and indirect relationships among constructs. Result. The findings indicate that extraversion personality significantly influences pro-environmental motivation and directly affects students’ engagement in environmental actions. Furthermore, pro-environmental motivation significantly mediates the relationship between extraversion and student engagement, highlighting the importance of internal motivational processes in translating personality traits into pro-environmental behavior. Conclusion. These results contribute to the literature on environmental psychology and educational behavior by demonstrating the dual pathway through which personality and motivation interact to promote student participation in sustainability initiatives. Implementation. Practically, the study underscores the importance of fostering intrinsic motivation alongside personality-sensitive strategies to strengthen youth engagement in environmental conservation programs.